أعمال عبد المنعم الخفاجي في الأدب العربي الحديث: دراسة تمهيدية وصفية: The Works of Abd al-Mun‘im al-Khafaji in Modern Arabic Literature: A Descriptive and Introductory Study (Al-Qamar, 2025)
This study explores the contributions of ʿAbd al-Munʿim al-Khafājī to modern Arabic literature, with a focus on his life, academic background, major writings, and his role in explaining and developing modern Arabic literary studies. Al-Khafājī represents a unique example of an Azhar-educated scholar who was deeply connected to Arabic literary heritage while also being aware of modern intellectual and cultural changes.The study follows a descriptive and analytical method and is mainly based on al-Khafājī’s own works as discussed in the thesis, along with a number of reliable modern academic sources. It is organized around three main areas: his biography and scholarly life, an overview of his varied publications, and a detailed discussion of four important books through which he addressed modern Arabic literature(Ma- Al shuara Al Muasreen,Madaris Ul Naqad Al Adabi Al Hadees,Min Tareekhna Al Muasir،  Dirasat fi- Al Adab al- Arbi Al Hadees wa Mdarishuu). These books show his interest in the rise of modern literature, its literary schools, its connection with social and intellectual change, and his call for a balanced approach that avoids both strict traditionalism and uncritical modernism.The study concludes that al-Khafājī played a significant role in clarifying the foundations of modern Arabic literary studies. Through his clear language, well-organized writing, and educational approach, he helped make modern Arabic literature easier to understand for students and researchers while maintaining academic quality. The study also emphasizes the need for further independent research on other aspects of his scholarly work, especially his contributions to poetry and literary criticism.
Keywords: Abd al-Mun`im Al khafaji, Modern Arabic literature, Ma- Al shuara Al Muasreen,Madaris Ul Naqad Al Adabi Al Hadees,Min Tareekhna Al Muasir, Dirasat fi- Al Adab al- Arbi Al Hadees wa Mdarishuu